2021
DOI: 10.1007/s00134-021-06562-4
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of oxygenation responses to proning and recruitment in COVID-19 pneumonia

Abstract: Purpose: This study aimed at investigating the mechanisms underlying the oxygenation response to proning and recruitment maneuvers in coronavirus disease 2019 (COVID-19) pneumonia.Methods: Twenty-five patients with COVID-19 pneumonia, at variable times since admission (from 1 to 3 weeks), underwent computed tomography (CT) lung scans, gas-exchange and lung-mechanics measurement in supine and prone positions at 5 cmH 2 O and during recruiting maneuver (supine, 35 cmH 2 O). Within the non-aerated tissue, we diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
77
3
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 50 publications
(92 citation statements)
references
References 40 publications
(41 reference statements)
6
77
3
6
Order By: Relevance
“…In summary, the improvement (or the lack of improvement) in oxygenation in COVID-19 patients depends on the interplay among the mechanisms described. At this stage of the disease (within 1 wk from intubation), the recruitment is one of the possibilities, but likely, not the most important, as strongly suggested by the lack of correlation between recruitment and oxygenation, a finding similar to what recently found with the CT scan in COVID-19 patients when studied at the same stage of the disease ( 14 , 15 ).…”
Section: Decrease Of the Total Chest Wall Compliancesupporting
confidence: 77%
See 1 more Smart Citation
“…In summary, the improvement (or the lack of improvement) in oxygenation in COVID-19 patients depends on the interplay among the mechanisms described. At this stage of the disease (within 1 wk from intubation), the recruitment is one of the possibilities, but likely, not the most important, as strongly suggested by the lack of correlation between recruitment and oxygenation, a finding similar to what recently found with the CT scan in COVID-19 patients when studied at the same stage of the disease ( 14 , 15 ).…”
Section: Decrease Of the Total Chest Wall Compliancesupporting
confidence: 77%
“…Finally, in late stages of the disease, the likelihood for oxygenation to improve with prone positioning becomes extremely low. We recently found that this phenomenon may be due to the progression of lung consolidation toward organizing fibrotic pneumonia ( 14 ).…”
Section: Decrease Of the Total Chest Wall Compliancementioning
confidence: 99%
“…In conclusion, orthodeoxia appears a common clinical feature of early COVID-19 pneumonia. This novel finding contributes to further distinguishing COVID-19 from other causes of ARDS [ 1 , 2 , 6 ], while reinforcing its advocated similarity with HPS [ 3 , 4 ]. Additionally, detecting orthodeoxia may help avoid awake-pronation when oxygenation simply benefits from recumbency: in a pandemic scenario, this possibly relevant clinical implication would deserve confirmation by larger studies.…”
mentioning
confidence: 69%
“…During proning, patients with and without orthodeoxia behaved similarly: respectively, 6 (46%) and 5 (36%) were prone responders ( p = 0.70, median PaO 2 increase 65[30–92] mmHg). This suggests that orthodeoxia cannot anticipate the response to proning, likely because of the unpredictable balance between perfusion redistribution and parenchymal reaeration in the ventral position [ 6 ]. However, the finding of orthodeoxia avoided overestimating the benefits of awake-pronation in 6 patients (22%) whose oxygenation improvement was due to lying recumbent at 0°, irrespective of prone or supine specifically (Fig.…”
mentioning
confidence: 99%
“…We read with interest the study done by Rossi et al recently published in Intensive Care Medicine [ 1 ]. In this study, the authors have studied the anatomical and physiological bases of oxygenation response to proning and recruitment maneuvers (RM) in acute respiratory distress syndrome (ARDS), by assessing gas exchange, lung mechanics, computed tomography (CT) chest scans and hemodynamics in coronavirus 2019 disease (COVID-19) patients with varied time period (3–24 days after hospital admission) [ 1 ]. Their findings are suggestive of lesser benefit of recruitment on oxygenation by the third week of illness in COVID ARDS.…”
mentioning
confidence: 99%